SHOTARA CHEMICAL COMPOSITION OF (FUMARIA VAILLANTII LOISEL) - Nasiba H. Karshibayeva; Nozimakhon A. Shodiyeva; Shakhlo M. Toshpulatova; Zarina K. Ibragimova (American Journal Of Agriculture And Horticulture Innovations, 2023)
This article discusses the chemical composition of shotara (Fumaria vaillantii Loisel.).